An innovation place model for the analysis of creativity and social innovativeness in selected French and Polish metropolises - Bierwiaczonek, Krzysztof; Pyka, Robert (Creativity Studies, 2023)
The article’s starting point is the assumption that, because of their socio-cultural and economic diversity, density, and complexity of interaction systems, metropolises provide a sufficient basis for creating innovation – including social innovation emerging from residents’ grassroots activities. Such perspective emphasises the importance of the creative potential of residents, as materialised in emerging innovation places and collectives operating and dispersed throughout the city. Assuming such a perspective made it possible to build an original model for this study of an innovation place that combines the features of classical and dynamic theories of place. In the empirical portion of the article, the data obtained during the study of ten selected innovation places located in three European metropolises are analysed. The study used qualitative methodology: in-depth interviews and observations. The study’s main objective was to assess the utility of the model of the innovation place as a tool for identifying and analysing metropolitan social innovation. This objective has been achieved, and the data obtained showed that, by using the model with characteristics typical of an innovation place, it is possible to effectively analyse the process of creating social innovation, indicate its determinants, and reveal differences in the innovation places under study.